Sustainability centres and fit: how centres work to integrate sustainability within business schools - Slager, Rieneke; Pouryousefi, Sareh; Moon, Jeremy; Schoolman, Ethan D. (Springer, 2018)
For nearly as long as the topic of sustainable business has been taught and researched in business schools, proponents have warned about barriers to genuine integration in business school practices. This article examines how academic sustainability centres try to overcome barriers to integration by achieving technical, cultural and political fit with their environment (Ansari, Fiss, & Zajac, 2010). Based on survey and interview data, we theorise that technical, cultural and political fit are intricately related, and that these interrelations involve legitimacy, resources and collaboration effects. Our findings about sustainability centres offer novel insights on integrating sustainable business education given the interrelated nature of different types of fit and misfit. We further contribute to the literature on fit by highlighting that incompatibility between strategies to achieve different types of fit may act as a source of dynamism.